Japanese Halal Food Production in Malaysia: Prospective Survey - Md Akhir, Md Nasrudin; Ishii, Yuka; Paidi, Rohayati; Hassan, Asmadi; Mohd Huda, Mohd Ikbal; Kassim, Siti Rohaini; Abdullah, Alias; Akhir, Azmi Mat (WILAYAH: The International Journal of East Asian Studies, 2011)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.